Relationship Between Coronavirus Anxiety and Sexual Quality of Life in Married Women - Sibel Dilmen and Nilufer Tugut (Professor Despina Sapountzi-Krepia, 2024)
Relationship Between Coronavirus Anxiety and Sexual Quality of Life in Married Women